Study on mechanical properties and fractal evolution law of containing tectonic coal combination - Qiudong SHAO; Wenbo PEI; Qiping LI; Xingpeng REN; Pengxiang ZHAO; Yanbiao TIAN; Li GUO (Meikuang Anquan)
To study the mechanical properties of tectonic coal combination specimens, based on the occurrence characteristics of coal seam in a high gas mine, this study carried out the mechanical properties test experiment of loading and fracture process of containing tectonic coal combination, and quantitatively analyzed the fracture evolution law of containing tectonic coal combination specimens by introducing fractal dimension. The results show that the compressive strength of the composite specimens containing tectonic coal is negatively correlated with the proportion of tectonic coal thickness, and the range of compressive strength variation corresponding to the proportion of structural coal thinkness from 0 to 100% is 22.94-7.65 MPa. The fractal dimensions of peak strain and peak stress point are positively correlated with the proportion of tectonic coal thickness, and the variation ranges of the fractal dimensions of the peak strain and peak stress points corresponding to the proportion of structural coal thickness from 0 to 100% are 1.21%-1.80% and 1.1714-1.1967, respectively; the fractal dimension of the composite specimens containing tectonic coal increases gradually with the increase of loading stress. The larger the proportion of tectonic coal thickness, the higher the complexity of the surface fracture development of the corresponding test piece when the fracture occurs.